Treatment of lung pulmonar hydatic echinococcosis in children - Benedictti, Juan Luis; Amoza, Benito; Bentancur, Bernabé (Cirugía del Uruguay, 1984)
Among the different surgicai procedures for. the treatment of the P.H.E., "puncture and extraction of hy• datlc cyst is the one propounded by the Children Surgí• cal Clinic. This procedure has had a low percentage of compli• cations andlor a second intervention and nil mortallty. Considerations are made about therapeutic policy in cases of bilateral P.H.E. or simultaneous to hepatic hidatic echinococcis.